Relasi Sosial Pemilik Usaha Dan Pekerja Keramba Ikan Di Pesisir Bintan (Studi Pada Desa mantang Besar kecamatan mantang kabupaten Bintan) - Sakila Sakila; Suryaningsih; Annissa Valentina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social relations between business owners and fish cage workers constitute an important aspect of sustaining aquaculture activities, particularly in coastal communities where employment relationships are strongly characterized by trust and mutual dependence. This study aims to describe the social relations between fish cage business owners and workers in Mantang Besar Village, Mantang District, Bintan Regency. The study employed a descriptive qualitative approach and was conducted in Mantang Besar Village. Informants were selected using a purposive sampling technique, involving two key informants who were chosen based on their direct involvement and comprehensive understanding of fish cage aquaculture activities. Data were collected through in-depth interviews and documentation and were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the social relationship between business owners and fish cage workers is established through continuous interactions and is predominantly characterized by cooperation based on mutual dependence. Business owners serve as providers of capital, production facilities, and decision-making authority, whereas workers contribute labor and technical skills in fish farming activities. Despite this reciprocal relationship, workers remain economically dependent on business owners due to unequal control over resources. Conflicts occur infrequently and are generally resolved through communication and deliberation. From Georg Simmel's perspective on social relations, the relationship between business owners and fish cage workers is dynamic, reflecting cooperation, domination, dependency, solidarity, and continuous adaptation to changing economic and social conditions within coastal communities.